(untitled) (Research, Society and Development, 2020)
The birth weight of newborn is an indicator that reflects maternal health conditions and the healthcare quality delivered during pregnancy. The aim of this study is to analyze the association between maternal consumption of cigarette during pregnancy and Low Birth Weight (LBW) in the Northeast of Brazil. Case-control study with the group of cases composed of 402 mothers with newborns with a birth weight <2,500 grams, and control composed of 1,210 mothers with newborns with weight ≥2,500 grams. Data were collected based on self-reported information by mothers and complemented with hospital records. Simple linear regression and logistic regression models were conducted. Majority of women were brown/ black, married, of low income and almost half of them had less than nine years of education. The consumption of 10 or more cigarettes a day was associated with LBW. For each cigarette added to the daily cigarette consumption there was a reduction of 18.6 grams in birth weight. Among mothers who smoked more than ten cigarettes per day, the mean reduction in birth weight was 283.1 grams. This study reinforces that LBW is associated with the maternal consumption of cigarettes.